Halomicrobium mukohataei gen. nov., comb. nov., and emended description of Halomicrobium mukohataei - (:unkn) unknown (MICROBIOLOGY SOC, 2002)
Haloarcula mukohataei, previously isolated from soils of salt flats in Argentina, was originally placed in the genus Haloarcula on the basis of 16S rRNA gene sequence comparison. However, its morphology and polar lipid composition differs from that of the other Haloarcula species. In addition, its phylogenetic distance from other Haloarcula species is rather large, and the 16S rDNA sequence does not contain many of the signature bases characteristic of the genus. Transfer of the species to a new genus was therefore recommended by the International Committee on Systematic Bacteriology Subcommittee on the taxonomy of Halobacteriaceae. A full description of the isolate, proposed as a member of a new genus, Halomicrobium, as Halomicrobium mukohataei comb. nov., is presented. The type strain is strain arg-2(T) (=JCM 9738(T)=DSM 12286(T) ATCC 700874(T)=NCIMB 13541(T)).
Keywords: Halomicrobium gen. nov.; Haloarcula mukohataei; Halomicrobium mukohataei comb. nov.; halophilic; archaea